2021
DOI: 10.1186/s12978-021-01254-0
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive counselling experiences in Spain in the process of creating a web-based contraceptive decision support tool: a qualitative study

Abstract: Background The choice of contraceptive method is a complex decision, and professionals should offer counselling based on the preferences, values and personal situation of the user(s). Some users are unsatisfied with the counselling received, which may, among other consequences, adversely affect method use adherence. In view of this situation, we propose exploring the experiences and needs of users and professionals for contraceptive counselling, in the context of creating a web-based contracept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
1
3
0
1
Order By: Relevance
“…Certain believes and myths(such as intake of oblation can prevent pregnancy), cultural practices, religious in uences(especially in Muslim community), pregnancy expectation early in marriage, fear of perceived side-effects(especially for IUCD), denial for female sterilization due to health conditions were some of the barriers to contraceptive use. Similar reasons were quoted by prior research, indicating that these barriers have not changed over time (11) (12) (13)(15)(16). Interestingly, the side-effects reported which in uenced women's utilization of any type of contraceptive were based on rumours and hearsay, rather than personal experience (14) (15).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Certain believes and myths(such as intake of oblation can prevent pregnancy), cultural practices, religious in uences(especially in Muslim community), pregnancy expectation early in marriage, fear of perceived side-effects(especially for IUCD), denial for female sterilization due to health conditions were some of the barriers to contraceptive use. Similar reasons were quoted by prior research, indicating that these barriers have not changed over time (11) (12) (13)(15)(16). Interestingly, the side-effects reported which in uenced women's utilization of any type of contraceptive were based on rumours and hearsay, rather than personal experience (14) (15).…”
Section: Discussionsupporting
confidence: 77%
“…However, in this study the providers indicated that practically it is very di cult to counsel due to lack of time and human resources. Few studies (14) (11) claimed that inadequate advice was offered by providers in the manner that they were most comfortable with, due to a lack of proper training or knowledge about other methods, thus preventing them from advising and administering customised contraceptives. This nding was also found in the current study, where the RMA stated that there was a lack of formal training in various contraceptive methods, which led to bias toward the only methods they were familiar with.…”
Section: Discussionmentioning
confidence: 99%
“…In Sierra Leone, proportion of younger women receiving good quality FP counselling services is higher compared to findings from countries in Sub-Saharan Africa such as Kenya (56.7%), Uganda (34.9%) and Senegal (18%) [ 8 , 29 , 39 ]. Furthermore, studies from other regions in countries such as Nepal and Spain indicated that the quality of FP counselling services were low and unsatisfactory based on the patient expectations and experience thus demanding for more information about the different methods [ 40 , 41 ]. The difference in the findings could probably be due to different study designs and populations.…”
Section: Discussionmentioning
confidence: 99%
“…Akseptor juga merasa penting mendapatkan informasi tentang kontrasepsi yang diberikan dan penggunaannya diberikan, walaupun di lapangan tidak selalu dilakukan dengan ideal seperti yang diharapkan oleh akseptor (Thongmixay et al, 2020). Kehandalan, perilaku, komunikasi, dan pendekatan yang tepat dari provider mempengaruhi nilai pelayanan dan kepuasan pengguna layanan kesehatan (Manzoor et al, 2019;Park et al, 2021;Reyes-Martí et al, 2021).…”
Section: Pembahasanunclassified